Urip Samadya Local Wisdom as A Strategy in Facing the Rise of The Hedonism Lifestyle and Global Development - Fateah, Nur; JA, Geovani (International Journal of Multidisciplinary Sciences, 2025)
The emergence of the ASEAN Economic Community (AEC) and international free trade has increased the flow of goods and services between countries. Indonesia has become a potential market for foreign products due to the domestic industry's inability to fully meet consumer demands. This situation is exacerbated by the rise of consumerism and hedonistic lifestyles among certain segments of society, which has weakened public appreciation for local products. This study aims to reexamine the relevance of the Javanese life philosophy urip samadya as a solution to the excessive consumption trend. The research employs a descriptive qualitative method with an ethnophilosophical approach. Data were collected through literature studies on Javanese philosophy and current consumption behavior. The results indicate that urip samadya, which emphasizes living in moderation and balance, offers a moral foundation for resisting excessive consumption. Living moderately encourages individuals to think rationally and maturely in distinguishing needs from mere desires. Furthermore, the teaching fosters introspective awareness regarding personal consumption patterns. The application of urip samadya not only strengthens individual character but also has the potential to revive appreciation for domestic products. This study concludes that revitalizing local wisdom such as urip samadya is highly relevant as a cultural strategy to foster conscious, ethical, and sustainable consumption in the face of globalization and the massive influx of imported goods.